Social Support Networks and Faculty Motivation: Insights from Tribhuvan University - Raut, Raju; Karkee, Anupama (NPRC Journal of Multidisciplinary Research, 2024)
Study examines the topic of “Social Support Networks and faculty Motivation." The research aims to shed light on the significant factors influencing teachers’ motivation within the context of Tribhuvan University. The study employed a quantitative research design, collecting data from a sample of teaching Faculty within the university. The study utilizes regression analysis to show the impact of four variables on the motivation levels of teaching faculty. SPSS 26 was used to analyze the data. The study revealed that family support and faculty-parent collaboration have a strong positive impact on faculty motivation. On the other hand, faculty -community relations and social recognition of faculty had less significant effects. These findings emphasize the importance of family encouragement and partnerships between faculty and parents in boosting faculty motivation. The study suggests that focusing on family support networks and improving teacher-parent cooperation can be effective ways to enhance faculty motivation in Tribhuvan University. Novelty: This research provides a new perspective i.e. Social Recognition, Faculty Community Relation, Faculty Parent Relation, and Family Support by studying the factors that influence faculty motivation specifically at Tribhuvan University.